LLGL2 Increases Ca2+ Influx and Exerts Oncogenic Activities via PI3K/AKT Signaling Pathway in Hepatocellular Carcinoma - Leng, Shusheng; Xie, Fei; Liu, Junyi; Shen, Junyi; Quan, Guangqian; Wen, Tianfu (Frontiers in Oncology, 2021)
ABSTRACT Background Lethal giant larvae (Lgl), scaffolding proteins, regulate the epithelial cell apicobasal polarity in Drosophila. They play important roles in asymmetric cell division, cell migration, and progenitor cells self-renewal as tumor suppressors. One of Lgl mammalian homologues proteins, LLGL2 overexpression has been reported in ER+ breast cancer and promotes tumor proliferation through regulating leucine uptake. Nonetheless, the role of LLGL2 in hepatocellular carcinoma (HCC) is still unknown. Methods TCGA dataset mining, qRT-PCR, Western blot along with immunohistochemistry assays were employed to explore LLGL2 expression in human HCC samples and cell lines. Moreover, the clinical value of LLGL2 was investigated in 156 HCC patients. Furthermore, the role as well as the molecular mechanism of LLGL2 in the progression of HCC was explored through a series of in vitro and in vivo experiments. Results LLGL2 was up-regulated in HCC tissues, which was related with certain clinicopathological features including tumor number, vascular invasion as well as advanced stage. High expression of LLGL2 predicted poor prognosis after hepatectomy. LLGL2 promoted HCC cells proliferation, migration and invasion through PI3K/ATK signaling by promoting calcium ion influx. Conclusion Our study identified that LLGL2 is a tumor promoter in HCC for the first time, which could potentially be utilized as a new biomarker and a therapeutic target for HCC.